Hermeneutika Simbol Kejahatan Menurut Paul Ricoeur - Joseph Kanar Tethool (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2022)
Paul Ricoeur was a French philosopher who lived in the 20th century. Ricoeur's distinctive thinking is found in his first work on the Philosophy of the Will. In this work, Ricoeur seeks to explore the problem of the fundamental structure of human will. He analyzes the human will which is nothing but an action. In carrying out actions, humans are always faced with desired and unwanted realities. Because human will is often faced with undesirable situations, humans fall into situations where they can make mistakes. This situation can be wrong to describe the existential situation of humans dealing with their human fragility and limitations. Fragile and limitations become the entrance for the presence of evil in humans. With his hermeneutics, Ricoeur finds evil in three forms of symbols, namely stains, sin and guilt. These three symbols of evil are evidence that humans acknowledge the existence of evil in their lives. Ricoeur also explained that the origin of crime was based on myths. In the end, evil still leaves a mystery that humans continue to struggle with. The struggle about the existence of evil actually shows the limitations of humans as created beings.